BIDADARI-BIDADARI SURGA INTRINSIC ELEMENTS: A NOVEL ANALYSIS - Lauren, Cendy (Lingual Journal of Language and Culture; Vol 7 No 1 (2019): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2019.v07.i01.p06, 2019)
Abstract This study aims to describe the intrinsic elements of Tere Liye's Bidadari-bidadari Surga novels. The method used to obtain data in this study is a qualitative descriptive method. Sources of data are excerpts of words, sentences, and discourses found in the novel Bidadari-Bidadari Surga by Tere Liye published by Republika in 2008. Related to the intrinsic elements that build literary works from within, data collection is done by reading data sources and researchers act as instruments. The researcher identifies, classifies, and codifies the data based on the problems studied. The data collection technique of this research uses textual techniques. Data analysis was carried out in a qualitative descriptive manner by reading, identifying, interpreting, and interpreting the data then drawing conclusions. The results of the analysis of this study show that the Bidadari-Bidadari Heaven novels have the theme of kinship and characters who are hard-nosed, not open, willing to sacrifice, kind-hearted, naughty, obedient, not deterred, and hardworking from several figures in the story. This novel is worth reading by teenagers, adults, the elderly and the elderly because this novel has a moral value that is very close to society.